Frecuencia de anticuerpos frente a neospora caninum en el ganado bovino de las provincias del Gualivá y bajo Magdalena del departamento de Cundinamarca, Colombia (2020)
The objective of this study was to determine the frequency of antibodies against Neospora caninum in the blood serum of cattle, in the Gualivá and Bajo Magdalena provinces of the Department of Cundinamarca, Colombia. A population of 182 Cebu cross-breeding cattle was selected, selected at random. To determine the frequency of antibodies, the study is divided into two phases: 1) Blood sampling 2) Evaluate the practices carried out by farmers through surveys. Once these two phases were carried out, the results were obtained, analyzed and tabulated. Of the 182 samples taken, 49 of them were positive for Neospora Caninum; being the municipality of Quebradanegra the one with the highest percentage obtained (33.33%) and the lowest conclusion value the municipality of Utica with (9.52%) of the positive samples, and an intermediate value of (28.5%) that corresponds to the municipalities of Caparrapí and Guaduas. When evaluating the possible risk factors for the presentation of Neospora Caninum, it can be concluded that the disposition of placentas and aborted fetuses, together with dogs, are the main source of contact.